Abundances of stream benthic macroinvertebrates influenced by four typical land cover types of the European Alps during an annual investigation in South Tyrol (Italy) - Alberto Scotti; Roberta Bottarin (PANGAEA, 2019)
Stream benthic macroinvertebrates have been collected at 14 sites in South Tyrol, on three different sampling occasions (May, July, September), year 2017. Considering the entire hydrological network of South Tyrol, sampling sites were selected according to the following requirements: 1) each sampling site had a homogeneous land cover type at reach scale (buffer area used of 1,000 m x 300 m), one among the types rocks (R), high alpine grasslands (G), coniferous forest (F), valley-bottom pastures (P); 2) the sampling sites had no glacial water source; 3) the sampling sites were situated max. 500 m from any road or trail (for access purpose); 4) for each of the four land cover types mentioned above, the most similar points in regards to landscape composition and topography calculated at the catchment scale were chosen. Organisms were collected through Surber samplings (0.0506 squared metres, mesh size 500 μm) in 3 rocks (R-5, R-29, R-52) and high alpine grasslands (G-133, G-188, G-193) sites, and in 4 coniferous forests (F-51, F-178, F-391, F-621) and valley bottom pastures (P-9, P-37, P-50, P-53) sites. Further details regarding the site selection and their characteristics are explained in the publication resulting from the analysis of this abundances data (see "Supplement to:").
Supplement to: Scotti, Alberto; Füreder, L; Marsoner, Thomas; Tappeiner, Ulrike; Stawinoga, A E; Bottarin, Roberta (2020): Effects of land cover type on community structure and functional traits of alpine stream benthic macroinvertebrates. Freshwater Biology, 65(3), 524-539, https://doi.org/10.1111/fwb.13448